Pengaruh Promosi, Persepsi Harga dan Kualitas Pelayanan terhadap Keputusan Pembelian di Restoran Peacock - Yuliana Dwi Marwa; Salman Paludi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study analyzes the effect of promotion, price perception, and service quality on purchasing decisions at Peacock Restaurant, The Sultan Hotel & Residence Jakarta. The increasingly intense competition in the restaurant industry encourages businesses to implement effective marketing strategies that are oriented toward consumer needs. These variables are selected because they are closely related to the considerations consumers make when choosing products or services. This research applies a quantitative approach using an purposive sampling technique with a total of 100 respondents. Data were collected from December 2025 to January 2026 through questionnaire distribution and analyzed using IBM SPSS version 26 through a series of assumption and hypothesis testing procedures. The findings indicate that promotion, price perception, and service quality have a positive and significant impact on purchasing decisions, both partially and simultaneously. The promotion variable was found to be the most dominant factor influencing purchase decisions, supported by the significant role of informal communication such as word of mouth. These findings indicate that purchase decisions can be enhanced through the optimization of promotional strategies, appropriate pricing aligned with perceived customer value, and the provision of consistent and high-quality services.